Językowe kontakty międzyetniczne we wspólnocie miejskiej warunkowane działalnością handlową w osiemnastowiecznym Wrocławiu = Inter-ethnic language relations in urban community conditioned by trading activities in the eighteenth-century Wroclaw - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses linguistic traces of multiethnic relations in an urban community determined by trading activities. The research is based on the 18th-century Polish-German phrasebook written by Jerzy Schlaga in Silesia, an ethnically and linguistically diverse region.
Keywords: językowe stosunki międzyetniczne; miejska wspólnota komunikatywna; zapożyczenia związane z handlem; Wrocław; 18 w.; inter-ethnic language relations; speech community; trade-related loanwords